Experimental Research on CO2 Pool Boiling Heat Transfer outside Horizontal Tube - Liu Shengchun; Li Lan; Ning Jinghong; Liu Jiangbin (Zhileng xuebao)
The pool boiling heat transfer of natural refrigerant CO2 outside single horizontal tube is investigated experimentally under different boiling pressure. Smooth tube and enhanced tube(Turbo-EHP) are taken as the single horizontal tube with electrical heating. The relationship of boiling heat transfer coefficient along with the heat flux and the boiling pressure is analyzed, and the heat transfer correlation of smooth tube under heat flux of 10~50 kW/m2 and boiling pressure of 2~4 MPa is obtained. The maximum error is 8.73% when the experimental values are compared with fitting formula. Compared with other existing heat transfer correlations, the new fitting formula of CO2 is matching very well, and the maximum error is 15%. In the range of experimental heat flux and boiling pressure, the overall heat transfer coefficients of the enhanced tube are higher than that of the smooth tube, and its enhancement factors varies from 1.50 to 1.72. This paper makes useful exploration of CO2 pool boiling heat transfer and will benefit the design of evaporator.